2006
DOI: 10.1021/cm060003w
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent Properties of (Sr, Zn)Al2O4:Eu2+,B3+ Particles as a Potential Green Phosphor for UV LEDs

Abstract: Sr 1-x , Zn x ) 1-y (Al 1.98 , B 0.02 )O 4 :Eu y 2+ green phosphor particles for ultraviolet light-emitting diodes (UV LEDs) were prepared by spray pyrolysis and their luminescent properties were investigated with changing the reducing temperature, the concentration of the activator, and the ratio of Sr to Zn. For the Sr(Al 1.98 , B 0.02 )O 4 :Eu 2+ phosphor, pure monoclinic SrAl 2 O 4 phase was formed when the post-treatment temperature was 1100-1200 °C. Over 1300 °C, however, the Sr 4 Al 14 O 25 phase appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(62 citation statements)
references
References 33 publications
1
61
0
Order By: Relevance
“…As we know, the PL intensity of the phosphor is strongly influenced by the activator concentration. [41][42][43] The PL intensities for the emission spectra clearly vary with changes in the Tb 3+ -doping concentration. As shown in Figure S6 (Supporting Information), the PL intensity first increases with an increase in the activator concentration, reaching a maximum value at 2 %, and then decreases with a further increase in the doping concentration.…”
Section: Resultsmentioning
confidence: 99%
“…As we know, the PL intensity of the phosphor is strongly influenced by the activator concentration. [41][42][43] The PL intensities for the emission spectra clearly vary with changes in the Tb 3+ -doping concentration. As shown in Figure S6 (Supporting Information), the PL intensity first increases with an increase in the activator concentration, reaching a maximum value at 2 %, and then decreases with a further increase in the doping concentration.…”
Section: Resultsmentioning
confidence: 99%
“…[31,32] The europium ions in the +2 oxidation states are mostly observed in aluminates and silicate matrices which require synthesis at high temperatures and reducing agents such as H 2 . [33][34][35] To our knowledge there are only two reports on the presence of Eu 2+ ions in GaN-based material, but no characteristic photoluminescence of Eu 2+ was observed. [36,37] The reason might be the existence of only small amount of Eu 2+ in their material, as stated by the authors.…”
Section: Introductionmentioning
confidence: 99%
“…It was clear that the substitution of boron was helpful for increasing the luminescent intensity. The phosphor for the WLEDs should have a good excitation spectrum in the wavelength from 370 to 410 nm [8]. So, the codoping of B 3+ (y = 0.08) greatly enhanced the excitation properties in the wavelength range shorter than 400 nm.…”
Section: Sample Characterizationmentioning
confidence: 99%
“…Q. Su et al prepared SrAl 2 O 4 : Eu 2+ phosphors, and found that it is a good green phosphor for a white LED excited with a UV-LED chip [6]. had increased the efficiency of SrAl 2 O 4 : Eu 2+ and extended its excitation band to a longer wavelength [7,8]. In previous investigations, the added B 2 O 3 is substituted in the AlO 4 framework of SrAl 2 O 4 , resulting in the enhancement of luminescence intensity at low concentration [9,10].…”
Section: Introductionmentioning
confidence: 99%